The Impact of CBLT Approaches on Students' Learning Achievements for ESP Courses - Muliati Muliati; Syarifuddin Dollah; Tamra Tamra; Ahmad Rossydi; St.Asriati AM (JURNAL ARBITRER, 2023)
ESP courses in higher education are seen as one of the efforts to provide undergraduates with skills beneficial to their careers to meet the growing demand of young professionals. The study assessed the impact of CBLT approaches on the student’s learning achievement in ESP courses. The objective of the study was to find out the impact of CBLT on students’ learning achievement in ESP courses. This study employed a qualitative method design that applied a case study design. The data source in this study was thirty students from different study programs who implemented CBLT approaches in learning ESP courses at Bosowa University. The study applied a questionnaire utilizing the five-point Likert Scale to see their responses on the student’s learning achievement in ESP courses through CBLT approaches. The interview results applied the Nvivo R1-5 to know in depth their responses on learning ESP courses through CBLT approaches. Three types of data coding are used namely, open coding, axial coding, and selective coding. Findings revealed that firstly, students believed that they could improve their English capability in learning ESP courses. Students were able to communicate in real life. Secondly, the findings revealed that students’ learning achievement on CBLT implementation can motivate students to learn ESP courses. Students believed that CBLT offers many opportunities for communication skills on ESP and use specific English in their disciplines.